HUBUNGAN STATUS GIZI DENGAN PERKEMBANGAN ANAK USIA 3-5 TAHUN DI PENDIDIKAN ANAK USIA DINI (PAUD) MIDANUTTA’LIM DESA MAYANGAN KECAMATAN JOGOROTO KABUPATEN JOMBANG - Putri Ramadhani, Hastuti; Ratnawati, Mamik; Alie, Hj.Yuliati (Jurnal Ilmiah Kesehatan (Journal of Health Sciences), 2017)
Nutrition is one determinant the quality of human resources, because undernourished will might cause failure growth and development on child. On child a preschool are the group that need attention will the nutrition, as they are in the growth and development. More than 50 % of the children was suffering from a development. The purpose of research to know nutritional status of relations with children growth a preschool age 3 to 5 years in Midanutta’lim Mayangan Village Subdistrict Jogoroto District Jombang. Method : The research use analytic correlation design with cross sectional approached. Population is all children aged 3 to 5 years in PAUD Midanutta’lim Mayangan Village Subdistrict Jogoroto District Jombang with 70 children, the sample as many as 35 children. Technique sampling used purposive sampling, the independent variable is status nutrition and dependent variable is the development of baby a preschool age 3 to 5 years. An instrument use Z-scor and KPSP. Data mixed with editing, coding, scoring, tabulating, analysis data using the spearman rank. Result and discussion : Based on the research done got that the majority of respondents (74.3%) a nutritional status of good, most respondents (68.6%) undergo development children appropriate, test results spearman rank got that α count smaller than α table that 0,001 < 0,05 which means H1 received and value correlation coefficient 0,557. The conclusion are powerful relationship between nutritional status of children growth preschool age 3 to 5 years . Based on the results of research is expected parents paying more attention to the nutritional intake in children especially at the age of a preschool because in this day and age that are the group vulnerable to nutrition problems will have an influence to the development of the baby.